THE EFFECT OF PRICE DISCOUNT, BONUS PACK, AND IN-STORE DISPLAY ON IMPULSE BUYING DECISIONS - Amirullah; Riswandhi; Febri Edward; M. Fadli Luran (LPPM Universitas Ibnu Sina, 2022)
Marketing activities are able to provide organizational growth. The purpose of this study was to determine the effect of discounts, bonus packages, and in-store signals on emergency pricing decisions. Residents of this study are customers of the Hypermart Mega Mall Batam, which employs 3000 people. The sample had 97 respondents, who were randomly sampled. Data analysis using multiple dosage tests and concepts using SPSS version 23. The results of this study concluded that the discounted discount, bonus package, and in-app display was timely. and a major impact on emergency purchases.